(untitled) (Alternautas, 2014)
Wellbeing is becoming an emerging concept representing a new paradigm that might help orient development policies. I believe indigenous people and social movements in Latin America are providing the case to rethink this debate in new light. I will explore how the Rarámuri people, like other minority groups living in the margins of nation-states and global markets, are constrained to act strategically to face political and socio-economic exclusion fluctuating between the tension of having the right to live differently and the need to be part of the larger society. Specifically, I want to explore how these wellbeing notions can be better understood if we consider the idea of the margins, as a conceptual space and as a place where notions (such as wellbeing) are created, configured and reconfigured by the articulations of forces that interact in dynamic and complex ways.